(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2025)
Tuberculosis meningitis (TBM) is an important global health challenge. It causes significant morbidity and mortality, especially in low and middle income countries. Its early recognition, diagnosis and management, continues to pose complex and challenging issues for healthcare teams and personnel. A better understanding of the global epidemiology of TB meningitis would help allocate appropriate healthcare resources for its management. Currently, diagnosis relies on a combination of clinical, radiological, and laboratory findings and needs to be made in timely fashion. A multidisciplinary approach is needed for optimal management and for preventing complications. Although progress has been made in recent years, several uncertain questions remain. HIV co-infection and increasing drug resistance, adds further complexity to any management decisions. This review would outline current knowledge, challenges and perspectives regarding the presentation, pathogen complications, diagnosis, treatment and control of TB meningitis, especially in relation to Asian countries.